2019
DOI: 10.20900/immunometab20190006
|View full text |Cite
|
Sign up to set email alerts
|

Complement and T Cell Metabolism: Food for Thought

Abstract: The classical complement system is engrained in the mind of scientists and clinicians as a blood-operative key arm of innate immunity, critically required for the protection against invading pathogens. Recent work, however, has defined a novel and unexpected role for an intracellular complement system-the complosome-in the regulation of key metabolic events that underlie peripheral human T cell survival as well as the induction and cessation of their effector functions. This review summarizes the current knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 90 publications
(125 reference statements)
1
14
0
Order By: Relevance
“…CD46 is absent in rodent somatic tissue in its "modern" form, and a functional homologue that fully recapitulates its activity has not yet been defined (Riley, Kemper, Leung, & Atkinson, 2002;Tsujimura et al, 1998;Yamamoto, Fara, Dasgupta, & Kemper, 2013). We will therefore focus in the following on human T-cells and only succinctly summarize the connection between the complosome and single-cell metabolism as more comprehensive reviews on this subject have recently been published (Hess & Kemper, 2016;West & Kemper, 2019;. Carrillo, 1979;Le Friec et al, 2012).…”
Section: The Complosome: Orchestrator Of Nutrient Usage and Metabolic Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…CD46 is absent in rodent somatic tissue in its "modern" form, and a functional homologue that fully recapitulates its activity has not yet been defined (Riley, Kemper, Leung, & Atkinson, 2002;Tsujimura et al, 1998;Yamamoto, Fara, Dasgupta, & Kemper, 2013). We will therefore focus in the following on human T-cells and only succinctly summarize the connection between the complosome and single-cell metabolism as more comprehensive reviews on this subject have recently been published (Hess & Kemper, 2016;West & Kemper, 2019;. Carrillo, 1979;Le Friec et al, 2012).…”
Section: The Complosome: Orchestrator Of Nutrient Usage and Metabolic Reprogrammingmentioning
confidence: 99%
“…Based on the location-driven activity of complement, its functionally important cross-activity with other intracellular danger sensor systems, and the emerging key role for all of these systems in cell physiology, we suggest that complement may have originally appeared in single-cell organisms as an intracellular sensor and rectifier of metabolic stress. With the evolution of into multi-organ organisms-and particularly with the development of a vascular system-complement took a bifurcated path: Part of the original C3 remained functional mostly within cells to control cell physiology, while part of C3 segregated into a secreted form, mostly produced by hepatocytes and assumed the role of the systemic pattern recognition system (Elvington, Liszewski, & Atkinson, 2016;Hess & Kemper, 2016;Kolev & Kemper, 2017;West et al, 2020;West & Kemper, 2019). We suggest that the structure and the posttranslational modifications of intra-and extra-cellular C3 is different: liver-derived C3 is folded into the classically known structure that can generate the opsonin C3b as well as the backbone for C3/C5 convertase formation.…”
Section: Intracellular Complement/the Complosome: Did It All Start Here?mentioning
confidence: 99%
“…It induces the proliferation and differentiation of T regulatory 1 cells, which produce large amount of IL10 and inhibit T cell activation. Therefore, reducing CD46 expression may increase T cell activation ( 3 , 30 , 54 , 55 ). Interestingly, while carbetocin’s signature profile was in support of a T cell activation hypothesis, Lopinavir and hydroxychloroquine were not.…”
Section: Discussionmentioning
confidence: 99%
“…Next to its well-known role, it has become evident that intracellular complement plays an important role in homeostasis [reviewed in ( 12 , 13 )]. It has been shown that complement proteins are expressed by a large variety of cells that secrete these proteins into the local environment when needed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that complement proteins are expressed by a large variety of cells that secrete these proteins into the local environment when needed. Recent studies also indicate that T cells not only express C3 but actually need intracellular C3 activation fragments for their survival ( 12 , 13 ). Next, complement receptor CD46, described in more detail below, has also been identified as an important player in T cell homeostasis ( 14 ).…”
Section: Introductionmentioning
confidence: 99%